Growth and Yield of Meranti Tomatoes (Lycopercium pipinelifoliu) Effect of Chrysanthemum Flower Waste Organic Fertilizer (Chrysanthemum morifolium) and Mutiara NPK Anorganic : Pertumbuhan dan Hasil Tomat Meranti (Lycopercium pipinelifoliu) Pengaruh Pupuk Organik Limbah Bunga Krisan (Chrysanthemum morifolium) dan Pupuk Anorganik NPK Mutiara - Purnamasari, Retno Tri; Hidayanto, Fajar; Rismanita, Dina (Journal of Applied Plant Technology, 2023)
The purpose of this study was to obtain the right dose of organic fertilizer combination of chrysanthemum flower waste and NPK Mutiara inorganic fertilizer to support the growth and efficiency of nutrient absorption levels of tomato meranti plants. The method used in this study was a complete randomized design (RAK) with 4 treatments and each treatment was repeated 6 time. The treatment made is P0: 500 kg ha-1 NPK Mutiara (100% NPK); P1: Dose of Organic Fertilizer Chrysanthemum Waste 15 Tons ha-1 + 25 % NPK; P2: Dose of Organic Fertilizer Chrysanthemum Waste 10 Tons ha-1 + 50 % NPK; P3: Dose of Organic Fertilizer Chrysanthemum Waste 5 Tons ha-1 + 75 % NPK. With observation parameters, namely plant height, number of leaves, leaf area, dry weight of upper plants, dry weight of lower plants, total dry weight of plants, leaf area index, net assimilation rate, and plant growth rate. The results showed that with the addition of organic matter of chrysanthemum waste fertilizer combined with NPK inorganic fertilizer was able to support the growth of meranti tomato plants in the vegetative phase of plants with a combined dose of chrysanthemum fertilizer 5 tons Ha-1 + 75% NPK showed the best results on plant height parameters, number of leaves and dry weight of plants.